2006
DOI: 10.1080/09273940600826471
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Detection of Multinucleated Giant Cells in the Conjunctiva of Patients with Sarcoidosis by In-Vivo Confocal Microscopy

Abstract: The utilization of IVCM to visualize the basic histology and pathology in sarcoidosis of the conjunctiva is novel. Initial results indicate that trained observers can detect MGCs in granulomatous inflammation. The ASL-1000 microscope tends to have better resolution and deeper penetration of the conjunctiva compared with the Confoscan 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In-vivo confocal microscopy of the conjunctiva was successfully used to identify the presence of multinucleated giant cells in patients with sarcoid conjunctival nodules with 100% specificity and 50% sensitivity. 67 The procedure required technical skills and may need an instrument with high resolution and deep penetration ability to improve a sensitivity of the test. Rose-Nussbaumer et al recently reported that anterior segment spectral-domain optical coherence tomography (OCT) could differentiate a predominantly mononuclear pattern of anterior chamber cells in active anterior uveitis associated with sarcoidosis or inflammatory bowel disease from a predominantly polymorphonuclear pattern in HLA-B27-related uveitis.…”
Section: Diagnosis Of Ocular Sarcoidosismentioning
confidence: 99%
“…In-vivo confocal microscopy of the conjunctiva was successfully used to identify the presence of multinucleated giant cells in patients with sarcoid conjunctival nodules with 100% specificity and 50% sensitivity. 67 The procedure required technical skills and may need an instrument with high resolution and deep penetration ability to improve a sensitivity of the test. Rose-Nussbaumer et al recently reported that anterior segment spectral-domain optical coherence tomography (OCT) could differentiate a predominantly mononuclear pattern of anterior chamber cells in active anterior uveitis associated with sarcoidosis or inflammatory bowel disease from a predominantly polymorphonuclear pattern in HLA-B27-related uveitis.…”
Section: Diagnosis Of Ocular Sarcoidosismentioning
confidence: 99%
“…For the first time, nCLE granuloma criteria were proposed and validated in a structured approach. Although previously several attempts were made, the proposed CLE granuloma descriptions varied widely and lacked consensus 15–19 . Initial experience with CLE‐imaging in the thorax was gained by inserting the CLE miniprobe through the bronchoscope's working channel and scanning the surface of the airway wall and lung nodules (probe‐based CLE [pCLE]).…”
Section: Discussionmentioning
confidence: 99%
“…With the upcoming of nCLE in interventional pulmonology, distinction on nCLE‐imaging between malignant and granulomatous criteria could be useful. Although some reports described cases of granulomatous CLE‐imaging, the granuloma descriptions vary widely without any consensus 15–19 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other non-invasive imaging tools and procedures have been used in ocular sarcoidosis such as conjunctiva's in vivo confocal microscopy for identifying multinucleated giant cells in patients. 33 However, as far as we know, no study has so far analyzed the relation between sarcoidosis and Meibomian glands function with meibography imaging.…”
Section: Discussionmentioning
confidence: 99%